(untitled) (Global Journal of Science Frontier Research, 2014)
The increase energy demand by the due to the growth of human population could cause decreasing fossil fuel energy. In near future energy demand will increase rapidly in the future. All those problems require each country to produce and to use renewal energy. Biogas is one of the renewable energy sources that can be used as the alternative energy. This is a kind of methane gas which is formed of various organic waste biomasses such as tofu waste. The aim of this research was to study the dynamic structure of methanogens community in the anaerobic digestion process by T-RFLP method. Sample was taken from anaerobic biodigester on day: 0, 5, 10, 15, and 20 to measure the pH, temperature, CH4, and molecular analysis. The dynamic of methanogens community during anaerobic digestion was observed by the TRFLP (Terminal Restriction Fragment Length Polymorphism) technique. The restriction enzyme used in that method was Alu1. The Shannon-Wiener (H’) index was used to analyze the community diversity.